An Introductory of the General Agreement on Tariffs and Trade and Their Dispute Settlement System - Montenegro, Juan Xavier Hermosa (Tirtayasa Journal of International Law, 2023)
In a general context, corresponds to a study of the World Trade Organization (WTO) and of its Dispute Settlement Understanding (DSU), and how does it work its Dispute Settlement body in the practice. In that light, is important to emphasize and recall the previous events that made the WTO what it is now. So, the aim of this research is how general approximation to study the General Agreement on Tariffs and Trade (GATT) and its Dispute Settlement System. This method used normative legal research. The research shows that The GATT 1947 and its dispute settlement system was in fact a big advance and change in the international trade history. Is remarkable this a “provisional” agreement lasted with full validity around 50 years, making the world trade a better place, mostly after those dark years of the World War II. So in fact, the GATT provide a effective way to deal with the daily outcomes of commerce not only in bilateral relation but in multilateral as well, providing clear rules to emphasize fair trade and tariffs in a secure and reliable way. Almost at the end of the so-called round of negotiations, the system showed some flaws that with the past of the time became more notorious.